2021
DOI: 10.1108/jwl-05-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

How a learning organization cultivates self-directed learning

Abstract: Purpose This study aims to provide empirical evidence of how the five disciplines of learning organization introduced by Senge (1990) are practiced and how it could cultivate self-directed learning among employees. Design/methodology/approach This qualitative study used a case study approach to get an in-depth understanding of how organizational learning is practiced in an innovative motorcycle-manufacturing company in Indonesia. A total of 30 staff and managers were selected purposively and interviewed by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…In the current volatile, uncertain, complex, and ambiguous (VUCA) environment, organisations, including universities as higher educational institutions, continuously need to anticipate, react, and respond accurately to remain competitive (Hutasuhut, Adruce & Jonathan, 2021). Exacerbated by the Coronavirus pandemic in 2019 , the challenges faced by university students are getting tougher.…”
Section: Introductionmentioning
confidence: 99%
“…In the current volatile, uncertain, complex, and ambiguous (VUCA) environment, organisations, including universities as higher educational institutions, continuously need to anticipate, react, and respond accurately to remain competitive (Hutasuhut, Adruce & Jonathan, 2021). Exacerbated by the Coronavirus pandemic in 2019 , the challenges faced by university students are getting tougher.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if a person often practices gratitude in their everyday lives, it will enable them to sustain healthy psychological well-being and happiness in life. Gratitude should be cultivated and encouraged as being the culture or climate of a university, as the previous study found the importance of context to individual learning (Hutasuhut, Adruce & Jonathan, 2021). Universities may promote gratitude practice by doing a campaign or various activities that involves gratitude, as gratitude has positive relationship with resilience and academic performance (Nailah Najwa, Hutasuhut, Mohamad Azhari, & Nurul Wardhani, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Autodidacts think in various ways, make library and internet searches, experimental studies in a certain area, filter and transform information from any source and anywhere (Tarhan, 2013). So, 21st-century learning activities should present autodidactic techniques like self-directed learning or independent learning (Ferri, 2021;Hutasuhut, Adruce & Jonathan, 2021). Self-directed learning requires the willing orientation of the student to different learning environments suitable for him/her.…”
Section: Discussionmentioning
confidence: 99%